Network-Based Expression Analyses and Experimental Verifications Reveal the Involvement of STUB1 in Acute Kidney Injury - Shi, Yanting; Chen, Genwen; Teng, Jie (Frontiers in Molecular Biosciences, 2021)
Acute kidney injury (AKI) is a severe and frequently observed condition associated with high morbidity and mortality. The molecular mechanisms underlying AKI have not been elucidated due to the complexity of the pathophysiological processes. Thus, we investigated the key biological molecules contributing to AKI based on the transcriptome profile. We analyzed the RNA sequencing data from 39 native human renal biopsy samples and 9 reference nephrectomies from the Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) and Gene Ontology (GO) analysis revealed that various GO terms were dysregulated in AKI. Gene set enrichment analysis (GSEA) highlighted dysregulated pathways, including “DNA replication”, “chemokine signaling pathway”, and metabolic pathways. Furthermore, the protein-to-protein interaction (PPI) networks of the DEGs were constructed, and the hub genes were identified using Cyotoscape. Moreover, Weighted gene co-expression network analysis (WGCNA) was performed to validate the DEGs in AKI-related modules. Subsequently, the upregulated hub genes STUB1, SOCS1 and VHL were validated as upregulated in human AKI and a mouse cisplatin-induced AKI model. Moreover, the biological functions of STUB1 were investigated in renal tubular epithelial cells. Cisplatin treatment increased STUB1 expression in a dose-dependent manner at both the mRNA and protein levels. Knockdown of STUB1 by siRNA increased the expression of proapoptotic Bax and cleaved Caspase-3 while decreasing antiapoptotic Bcl-2. In addition, silencing STUB1 increased the apoptosis of HK-2 cells and the proinflammatory cytokine production of IL6, TNFα and IL1β induced by cisplatin. These results indicated that STUB1 may contribute to the initiation and progression of AKI by inducing renal tubular epithelial cell apoptosis and renal inflammation.